2014
DOI: 10.1007/s00402-014-2108-3
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of acute and chronic anterior cruciate ligament reconstruction using LARS artificial ligaments: a randomized prospective study with a 5-year follow-up

Abstract: These results suggest that earlier ACL reconstruction using a LARS artificial ligament may provide an advantage in the treatment and rehabilitation of ACL rupture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 28 publications
1
43
0
1
Order By: Relevance
“…According to a review of the recent literature, the failure rate was 4.75% (23/484) in all studies where the mean follow-up was longer than 3 years (Table 3). [9,10,12,14–19] There were 9 cases of graft rupture and 14 cases of recurrent instability. Among these 9 cases, 6 were due to a new trauma, and 1 case was injury in a high-level sport activity.…”
Section: Discussionmentioning
confidence: 99%
“…According to a review of the recent literature, the failure rate was 4.75% (23/484) in all studies where the mean follow-up was longer than 3 years (Table 3). [9,10,12,14–19] There were 9 cases of graft rupture and 14 cases of recurrent instability. Among these 9 cases, 6 were due to a new trauma, and 1 case was injury in a high-level sport activity.…”
Section: Discussionmentioning
confidence: 99%
“…The LARS artificial ligament was made of polyethylene terephthalate, divided in two parts (intra-articular part and extra-articular part) [34]. Intra-articular part was composed of longitudinal external rotation fibers without transverse fibers as an imitation of ACL anatomic structure while extra-articular part was weaved by longitudinal and transverse fibers in order to avoid ligament deformation.…”
Section: Discussionmentioning
confidence: 99%
“…This is less than the pooled results of 1.7 mm reported in a meta-analyses of autograft ACLRs by Ardern et al 5 and comparable to the 1.2- to 2.38-mm side-to-side differences reported in previous LARS cohorts. 7,26,31,33 Increased translation with a KT-1000 arthrometer has been associated with anterior-to-posterior (AP) joint laxity more so than rotatory instability, and both are considered important for coupled motion of the knee. 10 Janssen et al 18 observed a significant relationship between pivot-shift laxity (grades 2 and 3) and reduced activity levels, so it is plausible that rotatory laxity might be a more crucial factor in determining higher level sports participation than purely AP joint laxity.…”
Section: Discussionmentioning
confidence: 99%